Derivatization of Azomethine Imines into beta-Aminocarbonyl Motifs - Betit, Lyanne (Université d'Ottawa / University of Ottawa, 2015)
β-Aminocarbonyl motifs are a privileged substructures in medicinal chemistry and peptidomimetics. As part of our efforts toward metal free aminations, we developed a method for intermolecular amino-carbonylation of alkenes using hydrazones. This method provides access to cyclic azomethine imines containing a β-aminocarbonyl motif. Conceptually, these dipoles can be derivatized into many bioactive compounds, such as 1,3-diamines, β-amino amides and β-amino acids. The first part of this thesis will present the results on the derivatization of our aminocarbonylation products into various nitrogen-containing molecules, such as β-amino amides, β-amino acids and pyrazolones. More specifically, a short, chromatography-free derivatization of azomethine imines into N-Boc-β-amino amides will be presented. Following these results, the next chapter will focus on attempts at develop novel aminocarbonylation reactivity between 1,2-diacylhydrazines and alkenes followed by results from our reductive N-N bond cleavage experiments on our cyclic hydrazides.
Keywords: Aminocarbonylation; Derivatization; beta-aminocarbonyl; Amino acids